Modelagem hidrodinâmica do rio Uruguai no trecho a jusante da UHE Foz do Chapecó - Pfeil, Luiz Eduardo Cavallo (2023)
The production of electricity is of great importance for the development of society. In Brazil, hydroelectric production stands out, responsible for more than 55% of the internal supply of energy. However, hydroelectric production is associated with several environmental impacts on the water body where it is installed. Upstream impacts are historically more studied, but downstream impacts are also significant and require more in-depth studies. Among them, the changes in the water regime, caused by flow pulses that derive from the energy production demanded at national level, stand out. The objective of this study is to structure a one-dimensional hydrodynamic model capable of simulating the flow pulses downstream of a hydroelectric plant that is intended to be built. The water body under study is the Uruguay River, in the stretch between Foz do Chapecó HPP and the fluviometric station Alto Uruguai (Code 74500000) located downstream of the Parque Estadual do Turvo (PET). This stretch is currently suffering the impacts of the flow pulses generated by the Foz do Chapecó HPP and has an ongoing construction project for the Itapiranga HPP, expected to be installed right upstream of the PET. To simulate the water regime of the stretch, the Hec Ras software was used. The model was built from topobathymetric data, obtained through interpolation, delimitation of the main channel, determination of Manning coefficients, determination of cross sections and other geometric characteristics requested by the model. The fluviometric data used in the model calibration were obtained for the stations of the UHE Foz do Chapecó Downstream (Code 74050000), Iraí (Code 74100000), Itapiranga (Code 74329000), Alto Uruguai (Code 74500000). in addition to the available stations for the tributary rivers to the section. Two simulations were carried out, the first (Simulation 1) was used in the model calibration and is related to the current flow regime, under the effect of flow pulses from the Foz do Chapecó HPP and the second (Simulation 2) related to the hypothetical flow regime, if a HPP is built in Itapiranga. The calibration results show simulated data consistent with those observed in the fluviometric stations of Iraí, Itapiranga and Alto Uruguai, with determination coefficients (R²) between 0.8562 and 0.9837 showing a good linear fit, Nash-Sutcliffe coefficients (NS) ranging from 0.8515 to 0.9832, proving the adequacy of the model, especially at higher flows, and the Nash-Sutcliffe logarithmic coefficient (NSlog), which ranged from 0.8557 to 0.9716, demonstrating the adequacy of the model also for the minimum flows Simulation of the current flow regime compared to the simulation of the hypothetical flow regime, in the case of the construction of an HPP in Itapiranga, showed that, in Salto do Yucumã, there is a tendency of increasing the maximum flow by 15.1%, reducing the minimum in 24.5%, and amplitude increase in 29.6%. The same occurred with the average maximum daily flows, which increased by 12.2%, while the average minimum daily flows were reduced by 27.2% and the amplitude between them increased by 122.2%.